Honduras : Request for a Stand-By Arrangement and an Arrangement Under the Standby Credit Facility. (IMF Staff Country Reports; Country Report ;, 2014)
The government of President Hernandez inherited a difficult macroeconomic situation upon taking office in January 2014. Economic growth decelerated significantly in 2013, driven mainly by lower private demand from policy uncertainty and by weaker trade-partner growth. The fiscal accounts weakened considerably in 2011-13, reflecting sizeable increases in government spending and in the deficit of the state-owned electricity company. The relaxation of fiscal policy has led to a rapid increase in public debt, which would continue into the medium term absent a change in economic policies. The balance of payments position has also weakened over the last three years, reflecting both expansionary macroeconomic policies and a less favorable terms of trade.